How Does AWWA's Small Systems Division Benefit Small Systems?. Issue 4 (6th May 2021) - Elliott, Stephanie; Macler, Bruce
Abstract : According to the US Environmental Protection Agency, there are about 35, 000 small community water systems (defined as serving fewer than 10, 000 people) and another 105, 000 noncommunity water systems that serve transient and workplace populations. Although these systems face most of the same challenges as larger water utilities, they generally have fewer resources to successfully address them. For the noncommunity systems especially, drinking water isn't usually even the principal reason they exist.